4D memristive chaotic system based optional parameterized random number generator - Gunakin, S.; Sahintekin, B.; Taskiran, Z. G. Cam (ELSEVIER, 2025)
In this study, a new memristive 4D dynamic system for use in multi-party security systems with multi-key scenarios is introduced. Time series analysis, phase portraits, Lyapunov properties, and bifurcation diagrams are mathematically investigated. The chaotic structure is verified by the Kaplan-Yorke dimension of 3.1805 and the high positive Lyapunov exponent. A memristor emulator that will provide the generation of memristive terms is designed and its characteristics are verified with experimentally. Using this emulator, a circuit that will realize the proposed 4D system analogously is also designed and SPICE simulations are performed. An optional parameterized random number generator is designed using the proposed system. The designed generator is run with different parameters to generate 1000 different random bit sequences and NIST randomness test was performed on these sequences. All of the generated sequences passed the NIST test and randomness is verified. In different statistical tests within NIST, a minimum of 909 and a maximum of 1000 number sequences passed the test with a success rate of over 95%. Thus, it is shown that the proposed system can be used as a random number generator in multi-user systems by changing the system parameters while preserving the structure of the proposed system.
Keywords: Chaos; Multi-party; Random number generator; Statistical test; Engineering